2009
DOI: 10.1128/jvi.02406-08
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Proline between Domains II and III of Hepatitis C Virus NS5A Influences both RNA Replication and Virus Assembly

Abstract: We previously demonstrated that two closely spaced polyproline motifs, with the consensus sequence Pro-X-X-Pro-X-Lys/Arg, located between residues 343 to 356 of NS5A, mediated interactions with cellular SH3 domains. The N-terminal motif (termed PP2.1) is only conserved in genotype 1 isolates, whereas the C-terminal motif (PP2.2) is conserved throughout all hepatitis C virus (HCV) isolates, although this motif was shown to be dispensable for replication of the genotype 1b subgenomic replicon. In order to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…NS5A contains a highly conserved C-terminal proline motif with the consensus sequence Pro-X-X-Pro-X-Arg that influences both RNA replication and viral assembly (26). This proline motif binds to the SH3 domains of the Src family kinase such as Fyn, Lyn, Hck, and Lck (27).…”
Section: Discussionmentioning
confidence: 99%
“…NS5A contains a highly conserved C-terminal proline motif with the consensus sequence Pro-X-X-Pro-X-Arg that influences both RNA replication and viral assembly (26). This proline motif binds to the SH3 domains of the Src family kinase such as Fyn, Lyn, Hck, and Lck (27).…”
Section: Discussionmentioning
confidence: 99%
“…For Western blotting, cells were lysed in GLB as described above at 48 h posttransfection. Virus harvest and titrations were performed as described (41).…”
Section: Methodsmentioning
confidence: 99%
“…In the earlier study using subgenomic replicon systems, HCV-NS5A was suggested to be involved in HCV RNA replication (8,(35)(36)(37)(38). Because HCV-NS5A contains multiple domains with specific functions, we attempted to determine the responsible domain(s) for regulation by ISG15 conjugation.…”
Section: Hcv-ns5a Is a Target Protein For Isg15 Conjugationmentioning
confidence: 99%